Metal adsorption type crack self-repairing material as well as preparation method and application thereof

By using metal adsorption crack self-repairing materials in cement-based materials, using the combination of granular foamed copper and sulfur aluminum cement fiber mortar, a rapid and continuous hydration reaction is achieved, and the crack self-repairing in the prior art is solved. The problem of durability significantly improves the recovery rate of flexural strength and the overall performance of the structure.

CN119241115APending Publication Date: 2025-01-03WUHAN METALLURGY ARCHITECTURE RES YUAN CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411317172.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03

Smart Images

  • Figure BDA0005052536770000081
    Figure BDA0005052536770000081
  • Figure BDA0005052536770000082
    Figure BDA0005052536770000082
  • Figure BDA0005052536770000091
    Figure BDA0005052536770000091
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and discloses a metal adsorption type crack self-repairing material and a preparation method and application thereof.The metal adsorption type crack self-repairing material is of a shell-core structure, an inner core comprises granular foamed copper and a strength repairing component adsorbed in the granular foamed copper, and a shell is made of sulfur aluminum cement fiber mortar; the strength recovery component is prepared from the following raw materials in parts by mass: 50 to 200 parts of ordinary Portland cement, 150 to 300 parts of aluminate cement, 100 to 250 parts of slaked lime and 10 to 30 parts of zeolite powder; the sulphoaluminate cement fiber mortar is prepared from the following raw materials in parts by mass: 400 to 500 parts of sulphoaluminate cement, 6 to 10 parts of chopped fiber, 500 to 600 parts of fine sand, 0.5 to 1.5 parts of thickening time control agent, 1 to 2 parts of water reducing agent and 100 to 120 parts of water. All the components of the crack self-repairing material are linked with one another, when a cement-based material cracks, all the components participate in the reaction sequentially and hierarchically, the conditions needed by the hydration reaction can be rapidly constructed, gel substances can be rapidly generated, and strong self-repairing of cracks is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to a metal adsorption type crack self-repairing material and a preparation method and application thereof. Background Art

[0002] Self-repair technology for cracks in cement-based materials has been a hot topic in the field of civil engineering research in recent years. Considering the ease of operation and potential practicality, complex crystallization self-repair technology and microbial encapsulation self-repair technology have been studied the most, and corresponding group standards have also been formulated and issued. The repair mechanism of the above two technologies is mainly to produce calcium carbonate crystals through complex crystallization and microbial mineralization to achieve the purpose of crack repair. Among them, related products of microbial self-repair technology have not yet been marketed and applied.

[0003] The self-repair technology of calcium carbonate crystal generation can restore the impermeability of cement-based material cracks to a certain extent, which has a good effect on the overall durability of the structure. However, the calcium carbonate formed in the short term cannot adhere firmly to both sides of the cracks. It only fills the cracks by blocking. Under the impact of high external water pressure or structural deformation, it is easy to be washed away or destroyed, causing the crack area to continue to be a weak area of ​​the structure. Therefore, how to make the cracks produce strong repairs is an issue that must be considered to enhance the practical value of self-repair technology. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a metal adsorption type crack self-repairing material and a preparation method and application thereof in view of the deficiencies in the prior art. The various components of the crack self-repairing material are closely linked. When the cement-based material cracks, the various components participate in the reaction in sequence and in a hierarchical manner, which can quickly build the conditions required for the hydration reaction, quickly produce gel-like substances, and achieve strong self-repair at the cracks.

[0005] In order to solve the technical problem raised by the present invention, the present invention provides a metal adsorption type crack self-repairing material, which has a core-shell structure, the inner core includes granular foamed copper and a strength repair component adsorbed in the granular foamed copper, and the outer shell is made of sulphoaluminum cement fiber mortar.

[0006] In the above scheme, the particle size of the crack self-repairing material is 4 to 7 mm, wherein the particle size of the granular foamed copper is 3 to 5 mm, and the thickness of the shell is 1 to 2 mm.

[0007] In the above scheme, the porosity of the granular copper foam is 50-70%, and the pore diameter is 0.1-0.5 mm.

[0008] In the above scheme, the strength recovery component includes the following raw materials in parts by weight: 50 to 200 parts of ordinary Portland cement, 150 to 300 parts of aluminate cement, 100 to 250 parts of slaked lime, and 10 to 30 parts of zeolite powder.

[0009] Furthermore, the particle size of the ordinary Portland cement is 3 to 32 μm.

[0010] Furthermore, the particle size of the aluminate cement is ≤3 μm.

[0011] Furthermore, the slaked lime is industrial grade slaked lime with a purity of ≥90% and a particle size of 38-45 μm.

[0012] Furthermore, the particle size of the zeolite powder is 5 to 10 μm.

[0013] Furthermore, the zeolite powder is modified zeolite powder, and the modification method is:

[0014] 1) Spreading dry natural zeolite powder on a flat surface and irradiating it with ultraviolet light;

[0015] 2) The zeolite powder irradiated with ultraviolet light is immersed in a saturated sodium carbonate solution, taken out, and dried to obtain modified zeolite powder.

[0016] Furthermore, the paving thickness of the natural zeolite powder is ≤1 mm.

[0017] Furthermore, during the ultraviolet irradiation, the ambient temperature is maintained at 30-50° C. and the irradiation time is 3-5 hours.

[0018] Furthermore, the mass ratio of the zeolite powder after ultraviolet irradiation to the saturated sodium carbonate solution is (0.8-1):1, and the soaking time is 24-36 hours.

[0019] In the above scheme, the mass ratio of the granular foamed copper to the strength recovery component is (0.9-1.1):1.

[0020] In the above scheme, the sulphoaluminate cement fiber mortar includes the following raw materials in parts by weight: 400-500 parts of sulphoaluminate cement, 6-10 parts of chopped fibers, 500-600 parts of fine sand, 0.5-1.5 parts of setting regulator, 1-2 parts of water reducer, and 100-120 parts of water.

[0021] Furthermore, the chopped fibers are polyvinyl alcohol fibers with a length of 6 to 8 mm.

[0022] Furthermore, the fine sand is quartz sand with a particle size of 40 to 80 meshes.

[0023] Furthermore, the setting regulator is aluminum sulfate and borax.

[0024] Preferably, the mass ratio of the aluminum sulfate to borax is (0.09-0.11):1.

[0025] Furthermore, the water reducing agent is a powdered polycarboxylic acid water reducing agent, and the water reducing rate is 35-40%.

[0026] In the above scheme, the final setting time of the sulphoaluminum cement fiber mortar is 30 to 60 minutes, and the 2h compressive strength is ≥35MPa.

[0027] The present invention also provides a method for preparing a metal adsorption type crack self-repairing material, comprising the following steps:

[0028] 1) ordinary Portland cement, aluminate cement, slaked lime and modified zeolite powder are mixed and stirred uniformly to obtain a strength recovery component;

[0029] 2) mixing the granular foamed copper and the strength recovery component uniformly, placing them in a vacuum environment for vacuum adsorption, taking them out, sieving them, and obtaining the inner core;

[0030] 3) mixing sulphoaluminate cement, chopped fibers, fine sand, setting regulator, water reducer and water, and stirring evenly to obtain sulphoaluminate cement fiber mortar;

[0031] 4) Wrap the sulphoaluminium cement fibre mortar on the inner core surface and scatter and air dry to obtain a metal adsorption type crack self-repairing material.

[0032] In the above scheme, in step 1), the stirring rate is 180-240 r / min, and the stirring time is 10-15 min.

[0033] In the above scheme, in step 2), the vacuum degree of vacuum adsorption is 0.0001-0.1 MPa, the vacuum temperature is 15-25° C., and the adsorption time is 20-24 h.

[0034] In the above scheme, in step 3), the stirring rate is 45 to 60 r / min and the stirring time is 2 to 3 min.

[0035] In the above scheme, in step 4), the air-drying time is 24 to 30 hours.

[0036] The present invention also provides an application of a metal adsorption type crack self-repairing material in crack self-repairing, and the application method is: replacing the sand in cement mortar or concrete with the crack self-repairing material to make the cement mortar or concrete have crack self-repairing performance.

[0037] In the above scheme, the amount of sand replaced by the crack self-repairing material is 8-10% of the mass of the sand.

[0038] In the above scheme, the crack self-repairing material can repair cracks with a width of ≤0.4 mm and restore the flexural strength to 25-35% of the original value.

[0039] The design concept of the present invention is as follows:

[0040] The present invention uses ordinary silicate cement and ordinary aluminate cement as strength development components, zeolite powder as an ion adsorption component, and slaked lime as a reaction enhancement component to form a strength recovery component; then granular foamed copper is used as an adsorption component, and the strength recovery component is adsorbed therein to form an inner core; finally, sulphoaluminium cement fibre mortar is used as a shell-forming component to form an outer shell outside the inner core to form a crack self-repairing material.

[0041] The copper foam used in the core of the present invention has excellent adsorption, ductility and toughness, can absorb a large amount of strength recovery components, and can guarantee the integrity of the self-repairing material particles to the greatest extent. It can play the role of a reaction bed when embedded in cement-based materials, and the defects caused by damage are minimal. The repair product grows stably and firmly in the copper foam. After the reaction, the copper foam becomes a ligament to restore the mechanical properties of the crack. The sulphoaluminum cement fiber mortar used in the shell can be hardened quickly through the use of a setting agent, locking the substances in the copper foam from leaking out, and the short-cut fibers can increase the toughness of the shell, making it less likely to be damaged. In addition, the shell material is consistent with the cement-based material in nature, and there will be no compatibility problems, nor will it deteriorate the performance of the cement-based material.

[0042] When the cement-based material cracks, the outer shell breaks first, while the foamed copper particles embedded on both sides of the crack have good toughness and can deform with the crack, increasing the space for the strength recovery component to dissolve; when water enters along the crack, the following series of reactions occur: 1) Due to the particle size ≤3μm, the aluminate cement dissolves completely the fastest, and quickly produces hydration products to fill the pores and defects of the foamed copper, first improving the mechanical properties of the foamed copper and inhibiting the further development of the crack; 2) Then the sodium carbonate in the modified zeolite powder dissolves to release initial sodium ions and carbonate ions; 3) Alkaline sodium ions promote the dissolution and hydration of ordinary silicate cement, and the cement particles of 3 to 32μm are the most active and can effectively participate in the hydration reaction to form the strongest cement stone structure, forming cement stone to further fill the pores of the foamed copper; 4) Carbonate ions react with calcium ions dissolved from the strength enhancement component and calcium ions in the solution continuously adsorbed by the ion adsorption component to form carbonate crystals, and the generated crystals continue to fill the remaining pores of the foamed copper until a dense structure is formed, thereby restoring the mechanical properties of the cracks. Through sequential, layered, rapid and continuous reactions, strong self-repair of the cracks is achieved, solving the problem that filling-type repairs such as complex crystallization self-repair and microbial self-repair are not durable and resistant to erosion.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The present invention uses ordinary silicate cement and ordinary aluminate cement as strength development components, zeolite powder as ion adsorption component, and slaked lime as reaction enhancement component to form a strength recovery component; then granular foamed copper is used as an adsorption component to adsorb the strength recovery component therein to form an inner core; finally, sulphoaluminium cement fibre mortar is used as a shell-making component to form an outer shell outside the inner core to form a crack self-repairing material. The crack self-repairing material is manufactured through the interlocking structure of each component. When the cement-based material cracks, each component participates in the reaction in sequence and in a hierarchical manner, which is both fast and continuous, and can quickly build the conditions required for the hydration reaction, quickly produce gel-like substances, and achieve strong self-repair at the cracks, solving the problem that filling-type repairs such as complex crystallization self-repair and microbial self-repair are not durable and resistant to erosion. DETAILED DESCRIPTION

[0045] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0046] In the following embodiments, the particle size of the granular foamed copper used is 3-5 mm, the porosity is 50-70%, and the pore size is 0.1-0.5 mm; the particle size of ordinary Portland cement is 3-32 μm; the particle size of aluminate cement is ≤3 μm; the slaked lime is industrial grade slaked lime with a purity of ≥90% and a particle size of 38-45 μm; the particle size of natural zeolite powder is 5-10 μm; the sulphoaluminate cement is R.SAC 42.5; the short-cut fiber is polyvinyl alcohol fiber with a length of 6 mm; the fine sand is quartz sand with a particle size of 40-80 mesh; the setting agent is aluminum sulfate and borax with a mass ratio of 0.1:1; the water reducer is a powdered polycarboxylic acid water reducer with a water reduction rate of 38%.

[0047] Example 1

[0048] A metal adsorption type crack self-repairing material has a core-shell structure, wherein the core comprises granular foamed copper and a strength repair component adsorbed in the granular foamed copper, and the shell is made of sulphur-aluminium cement fiber mortar.

[0049] The strength recovery component includes the following raw materials in parts by mass: 200 parts of ordinary Portland cement, 150 parts of aluminate cement, 150 parts of slaked lime, and 10 parts of modified zeolite powder.

[0050] The preparation method of modified zeolite powder is:

[0051] 1) Spread the natural zeolite powder dried to constant weight at 105°C and sieved on a flat surface with a spreading thickness of 0.6-0.8 mm, maintain an ambient temperature of 40±2°C, and irradiate the spread zeolite powder with ultraviolet light to clear and increase the absorption channels of the zeolite powder for 4 hours;

[0052] 2) Soaking the zeolite powder after ultraviolet irradiation in a saturated sodium carbonate solution, the mass ratio of the zeolite powder after ultraviolet irradiation to the saturated sodium carbonate solution is 0.8:1, taking out after soaking for 24 hours, and drying at 105° C. to constant weight to obtain modified zeolite powder.

[0053] The sulphoaluminum cement fiber mortar includes the following raw materials in parts by mass: 400 parts of sulphoaluminate cement, 6 parts of chopped fibers, 500 parts of fine sand, 1 part of setting regulator, 1.2 parts of water reducer, and 120 parts of water. After testing, the final setting time of the sulphoaluminum cement fiber mortar is 42 minutes, and the 2-hour compressive strength is 40 MPa.

[0054] The method for preparing the metal adsorption type crack self-repairing material of this embodiment comprises the following steps:

[0055] 1) Put ordinary Portland cement, aluminate cement, slaked lime and modified zeolite powder into a vertical mixer, start stirring at a speed of 180 r / min for 10 min to obtain a strength recovery component;

[0056] 2) Place the granular foamed copper and the strength recovery component in a vacuum drying oven at a mass ratio of 1.1:1 for vacuum adsorption, with a vacuum degree of 0.01 MPa and a vacuum temperature of 20±5°C. Take them out after adsorption for 20 hours, pass them through a 2.36 mm sieve, and take the material on the sieve to obtain the core;

[0057] 3) mixing sulphoaluminate cement, chopped fibers, fine sand, setting regulator and water, and stirring at a stirring speed of 45 r / min for 2 min to obtain sulphoaluminate cement fiber mortar;

[0058] 4) Wrap the sulphoaluminium cement fibre mortar on the inner core surface with a wrapping thickness of 1.5 mm, scatter and air-dry for 26 hours, and obtain a metal adsorption type crack self-repairing material with a particle size of 4.5 to 6.5 mm.

[0059] Example 2

[0060] A metal adsorption type crack self-repairing material has a core-shell structure, wherein the core comprises granular foamed copper and a strength repair component adsorbed in the granular foamed copper, and the shell is made of sulphur-aluminium cement fiber mortar.

[0061] The strength recovery component includes the following raw materials in parts by mass: 100 parts of ordinary Portland cement, 250 parts of aluminate cement, 100 parts of slaked lime, and 20 parts of modified zeolite powder.

[0062] The preparation method of modified zeolite powder is:

[0063] 1) Spread the natural zeolite powder dried to constant weight at 105°C and sieved on a flat surface with a spreading thickness of 0.6-0.8 mm, maintain the ambient temperature at 35±2°C, and irradiate the spread zeolite powder with ultraviolet light to clear and increase the absorption channels of the zeolite powder for 5 hours;

[0064] 2) The zeolite powder irradiated by ultraviolet light was immersed in a saturated sodium carbonate solution, the mass ratio of the zeolite powder irradiated by ultraviolet light to the saturated sodium carbonate solution was 0.9:1, and after immersion for 30 hours, the powder was taken out and dried at 105° C. to constant weight to obtain a modified zeolite powder.

[0065] The sulphoaluminum cement fiber mortar includes the following raw materials in parts by mass: 450 parts of sulphoaluminate cement, 8 parts of chopped fibers, 550 parts of fine sand, 0.5 parts of setting regulator, 1.5 parts of water reducer, and 110 parts of water; after testing, the final setting time of the sulphoaluminum cement fiber mortar is 55 minutes, and the 2-hour compressive strength is 35 MPa.

[0066] The method for preparing the metal adsorption type crack self-repairing material of this embodiment comprises the following steps:

[0067] 1) ordinary Portland cement, aluminate cement, slaked lime and modified zeolite powder are put into a vertical mixer, and stirring is started at a speed of 240 r / min for 15 min to obtain a strength recovery component;

[0068] 2) Place the granular foamed copper and the strength recovery component in a vacuum drying oven at a mass ratio of 1:1 for vacuum adsorption, with a vacuum degree of 0.001 MPa and a vacuum temperature of 22±3°C. Take them out after adsorption for 22 hours, pass them through a 2.36 mm sieve, and take the material on the sieve to obtain the core;

[0069] 3) mixing sulphoaluminate cement, chopped fibers, fine sand, setting regulator and water, and stirring at a stirring speed of 55 r / min for 2.5 min to obtain sulphoaluminate cement fiber mortar;

[0070] 4) Wrap the sulphoaluminium cement fibre mortar on the inner core surface with a wrapping thickness of 1 mm, scatter and air-dry for 30 hours, and obtain a metal adsorption type crack self-repairing material with a particle size of 4 to 6 mm.

[0071] Example 3

[0072] A metal adsorption type crack self-repairing material has a core-shell structure, wherein the core comprises granular foamed copper and a strength repair component adsorbed in the granular foamed copper, and the shell is made of sulphur-aluminium cement fiber mortar.

[0073] The strength recovery component includes the following raw materials in parts by mass: 50 parts of ordinary Portland cement, 300 parts of aluminate cement, 250 parts of slaked lime, and 30 parts of modified zeolite powder.

[0074] The preparation method of modified zeolite powder is:

[0075] 1) Spread the natural zeolite powder dried to constant weight at 105°C and sieved on a flat surface with a spreading thickness of 0.6-0.8 mm, maintain an ambient temperature of 45±2°C, and irradiate the spread zeolite powder with ultraviolet light to clear and increase the absorption channels of the zeolite powder for 3 hours;

[0076] 2) The zeolite powder irradiated by ultraviolet light was immersed in a saturated sodium carbonate solution, the mass ratio of the zeolite powder irradiated by ultraviolet light to the saturated sodium carbonate solution was 1:1, and the powder was taken out after immersion for 36 hours, and dried at 105° C. to constant weight to obtain a modified zeolite powder.

[0077] The sulphoaluminum cement fiber mortar includes the following raw materials in parts by mass: 500 parts of sulphoaluminate cement, 10 parts of chopped fibers, 500 parts of fine sand, 1.5 parts of setting regulator, 2 parts of water reducer, and 100 parts of water; after testing, the final setting time of the sulphoaluminum cement fiber mortar is 35 minutes, and the 2-hour compressive strength is 45 MPa.

[0078] The method for preparing the metal adsorption type crack self-repairing material of this embodiment comprises the following steps:

[0079] 1) Put ordinary Portland cement, aluminate cement, slaked lime and modified zeolite powder into a vertical mixer, start stirring at a speed of 220 r / min for 12 min to obtain a strength recovery component;

[0080] 2) placing the granular foamed copper and the strength recovery component in a mass ratio of 0.9:1 in a vacuum drying oven for vacuum adsorption, with a vacuum degree of 0.0001 MPa and a vacuum temperature of 23±2°C. After adsorption for 24 hours, the copper was taken out and passed through a 2.36 mm sieve, and the material on the sieve was taken to obtain the core;

[0081] 3) Mix sulphoaluminate cement, chopped fibers, fine sand, setting agent and water and stir at a stirring speed of 60 r / min for 3 min to obtain sulphoaluminate cement fiber mortar; stirring speed and time

[0082] 4) Wrap the sulphoaluminium cement fibre mortar on the inner core surface with a wrapping thickness of 2 mm, scatter and air-dry for 24 hours, and obtain a metal adsorption type crack self-repairing material with a particle size of 5 to 7 mm.

[0083] Application Examples 1 to 3

[0084] The metal adsorption type crack self-repairing materials prepared in Example 1, Example 2, and Implementation 3 were respectively applied to standard cement mortar. The application method was: the crack self-repairing materials were used to replace the sand in the standard cement mortar, and the replacement amounts were 8%, 10%, and 10% of the sand mass, respectively.

[0085] Comparative Example 1

[0086] Comparative Example 1 is a standard cement mortar without applying crack self-repairing material.

[0087] Comparative Example 2

[0088] Comparative Example 2 uses the complex crystal material XYPEX as the crack self-repairing material, and the method of using it is to add 1.5% of the mass of cement into the cement standard mortar.

[0089] Comparative Example 3

[0090] The only difference between Comparative Example 3 and Application Example 1 is that when preparing the metal adsorption type crack self-repairing material, the particle size of ordinary Portland cement used is 0-80 μm, of which the mass proportion of 3-32 μm is only 45%.

[0091] Comparative Example 4

[0092] The only difference between Comparative Example 4 and Application Example 1 is that when the metal adsorption type crack self-repairing material is prepared, the modified zeolite powder used is not irradiated with ultraviolet rays during the preparation process.

[0093] Comparative Example 5

[0094] The only difference between Comparative Example 5 and Application Example 1 is that when preparing the metal adsorption type crack self-repairing material, the modified zeolite powder used is not immersed in a saturated sodium carbonate solution.

[0095] Comparative Example 6

[0096] The only difference between Comparative Example 6 and Application Example 1 is that when preparing the metal adsorption type crack self-repairing material, the foam copper and the strength recovery component are mixed evenly and then not vacuum adsorbed, but naturally adsorbed for 20 hours at normal pressure and temperature of 20±5°C.

[0097] The flexural strength of the cement mortar obtained in each application example and comparative example was tested after standard curing for 28 days, and then the tested specimens were fixed into a whole with a spring pressure device, and the crack width at the break was controlled to be 0.3-0.4 mm. The flexural strength was tested after standard curing for 7 days and 28 days. The results are shown in Tables 1 and 2.

[0098] Table 1 Comparison of crack recovery

[0099]

[0100] Table 2 Comparison of strength recovery

[0101]

[0102]

[0103] As shown in Tables 1 and 2, the crack width repair rates of Comparative Example 1 at 7d and 28d are only 7.7% and 12.8%, and the flexural strength recovery rates at 7d and 28d are both 0, indicating that the self-repair ability of the standard mortar is very poor. Although the crack width repair rate of Comparative Example 2 is better, the flexural strength recovery rates at 7d and 28d are also 0, indicating that its crack repair form is only filling type and cannot restore the mechanical properties at the crack. Comparative Example 3 uses ordinary Portland cement with conventional particle size, and its reaction activity is relatively slow, which has little effect on filling type repair, but the mechanical property recovery rates at 7d and 28 are only 10.4% and 13.0%, respectively. Comparative Example 4 does not use ultraviolet irradiation modification to further enhance the adsorption performance of zeolite powder. In Comparative Example 5, zeolite powder does not adsorb strong alkaline ions and cannot further promote the occurrence of hydration reaction. Therefore, the crack filling performance of both after reaction is acceptable, but the recovery rates of mechanical properties at 28d are less than 20%, which are 19.0% and 14.1%, respectively. In Comparative Example 6, since vacuum adsorption was not used, the strength recovery substances stored in the foamed copper were limited, and the reaction products were relatively small, which not only affected the crack width repair reduction to a certain extent, but also the mechanical property recovery rate was only 5.0%. In comparison, Application Examples 1 to 3 not only had a better crack width repair effect, but also the 7d and 28d flexural strength recovery rates were both over 25%, indicating that the self-repairing material of the present invention can promote the strength recovery of the cement-based material cracks, help maintain the overall performance of the structure, and have more practical application value, unlike the undoped self-repairing material or the complex crystallization crack filling self-repairing material.

[0104] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A metal adsorption type crack self-repairing material, characterized in that: It has a core-shell structure, the inner core includes granular foamed copper and a strength repair component adsorbed in the granular foamed copper, and the outer shell is made of sulphoaluminum cement fiber mortar; the strength recovery component includes the following raw materials in parts by mass: 50-200 parts of ordinary Portland cement, 150-300 parts of aluminate cement, 100-250 parts of slaked lime, and 10-30 parts of zeolite powder; the sulphoaluminum cement fiber mortar includes the following raw materials in parts by mass: 400-500 parts of sulphoaluminate cement, 6-10 parts of chopped fibers, 500-600 parts of fine sand, 0.5-1.5 parts of setting regulator, 1-2 parts of water reducer, and 100-120 parts of water.

2. The metal adsorption type crack self-repairing material according to claim 1, characterized in that: The zeolite powder is modified zeolite powder, and the modification method comprises the following steps: 1) Spreading dry natural zeolite powder on a flat surface and irradiating it with ultraviolet light; 2) The zeolite powder irradiated with ultraviolet light is immersed in a saturated sodium carbonate solution, taken out, and dried to obtain modified zeolite powder.

3. The metal adsorption type crack self-repairing material according to claim 2, characterized in that: The paving thickness of the natural zeolite powder is ≤1mm; the ambient temperature is maintained at 30-50°C during the ultraviolet irradiation, and the irradiation time is 3-5h; the mass ratio of the zeolite powder after ultraviolet irradiation to the saturated sodium carbonate solution is (0.8-1):1, and the soaking time is 24-36h.

4. The metal adsorption type crack self-repairing material according to claim 1, characterized in that: The particle size of the crack self-repairing material is 4-7 mm, wherein the particle size of the granular foamed copper is 3-5 mm, and the thickness of the shell is 1-2 mm.

5. The metal adsorption type crack self-repairing material according to claim 1, characterized in that: The porosity of the granular foamed copper is 50-70%, and the pore size is 0.1-0.5 mm; the mass ratio of the granular foamed copper to the strength recovery component is (0.9-1.1):

1.

6. The metal adsorption type crack self-repairing material according to claim 1, characterized in that: The particle size of the ordinary Portland cement is 3-32 μm; the particle size of the aluminate cement is ≤3 μm; the slaked lime is industrial grade slaked lime with a purity of ≥90% and a particle size of 38-45 μm; and the particle size of the zeolite powder is 5-10 μm.

7. The metal adsorption type crack self-repairing material according to claim 1, characterized in that: The final setting time of the sulphoaluminium cement fiber mortar is 30 to 60 minutes, and the 2h compressive strength is ≥35MPa; the chopped fibers are polyvinyl alcohol fibers with a length of 6 to 8mm; the fine sand is quartz sand with a particle size of 40 to 80 meshes; the setting regulators are aluminium sulfate and borax, and the mass ratio of aluminium sulfate to borax is (0.09 to 0.11):1; the water reducer is a powdered polycarboxylic acid water reducer, and the water reduction rate is 35 to 40%.

8. A method for preparing the metal adsorption type crack self-repairing material according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) ordinary Portland cement, aluminate cement, slaked lime and modified zeolite powder are mixed and stirred uniformly to obtain a strength recovery component; 2) mixing the granular foamed copper and the strength recovery component uniformly, placing them in a vacuum environment for vacuum adsorption, taking them out, sieving them, and obtaining the inner core; 3) mixing sulphoaluminate cement, chopped fibers, fine sand, setting regulator, water reducer and water, and stirring evenly to obtain sulphoaluminate cement fiber mortar; 4) Wrap the sulphoaluminium cement fibre mortar on the inner core surface and scatter and air dry to obtain a metal adsorption type crack self-repairing material.

9. The method for preparing the metal adsorption type crack self-repairing material according to claim 8, characterized in that: In step 1), the stirring rate is 180-240 r / min, and the stirring time is 10-15 min; in step 2), the vacuum degree of vacuum adsorption is 0.0001-0.1 MPa, the vacuum temperature is 15-25° C., and the adsorption time is 20-24 h; in step 3), the stirring rate is 45-60 r / min, and the stirring time is 2-3 min; in step 4), the air-drying time is 24-30 h.

10. An application method of the metal adsorption type crack self-repairing material according to any one of claims 1 to 7, characterized in that: The sand in cement mortar or concrete is replaced by crack self-repairing materials to make the cement mortar or concrete have crack self-repairing properties.